Contemporary Art from Germany : German Festival in India 2000 - 2001. - Vitali, Christoph; National Gallery of Modern Art, Mumbai; Birla Academy of Art & Culture, Calcutta; Karnataka Chitrakala Parishath Art Complex, Bangalore; National Gallery of Modern Art, New Delhi (München : Goethe-Institut München, 2000)
Schumacher, Emil ; Beuys, Joseph ; Heisig, Bernhard ; Graubner, Gotthard ; Uecker, Günther ; Becher, Bernd & Hilla ; Richter, Gerhard ; Antes, Horst ; Baselitz, Georg ; Rückriem, Ulrich ; Penck, A.R. ; Gerz, Jochen ; Knoebel, Imi ; Darboven, Hanne ; Lüpertz, Markus ; Polke, Sigmar ; Horn, Rebecca ; Immendorff, Jörg ; Kiefer, Anselm ; Sieverding, Katharina ; Förg, Gunther ; Metzel, Olaf ; Trockel, Rosemarie ; Kippenberger, Martin ; Gursky, Andreas ; Fritsch, Katharina ; Ruff, Thomas ; Rauch, Neo ; Richter, Daniel ; Kowski, Uwe
Engels
Contemporary Art from Germany : German Festival in India 2000-2001, National Gallery of Modern Art, Mumbai, October 3 - November 19, 2000 ; Birla Academy of Art & Culture, Calcutta, December 4, 2000 - January 3, 2001 ; Karnataka Chitrakala Parishath Art Complex, Bangalore, January 19 - February 15, 2001 ; National Gallery of Modern Art, New Delhi, March 2 - March 31, 2001
boek
Keywords: Duitsland; India